PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS INKUIRI TERBIMBING MATERI ZAT ADIKTIF DAN PSIKOTROPIKA UNTUK SISWA KELAS XI SMA - Yulia Dewi Astuti; Triana Asih; Muhfahroyin Muhfahroyin (EDUBIOLOCK, 2022)
The purpose of this research development is to produce teaching material products in the form of interactive inquiry-based e-modules guided by addictive substances and psychotropic substances to assist the learning process. This type of research uses a 4-D development model consisting of 4 stages, namely define, design, development, and disseminate, the research is carried out only until the development stage. The interactive e-module is accessed via a google drive link. The development of interactive e-modules produced through the validation stages, namely validation of material experts, validation of design experts, and student response trials. Validation from material experts gets a percentage of 95%, for design experts scores a percentage of 95%, and student response trials are 93%. Based on the percentage obtained, this learning media is included in the "Very Good" category so that it is suitable for use in the learning process.